2012
DOI: 10.2307/41703483
|View full text |Cite
|
Sign up to set email alerts
|

Building Member Attachment in Online Communities: Applying Theories of Group Identity and Interpersonal Bonds

Abstract: Online communities are increasingly important to organizations and the general public, but there is little theoretically based research on what makes some online communities more successful than others. In this article, we apply theory from the field of social psychology to understand how online communities develop member attachment, an important dimension of community success. We implemented and empirically tested two sets of community features for building member attachment by strengthening either group iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
346
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 465 publications
(396 citation statements)
references
References 85 publications
15
346
0
4
Order By: Relevance
“…Accordingly, a possible explanation for the difference is that some expectant mothers are more easily induced to feel happy and satisfied with online social life given the same level of self-esteem. Ren et al's (2012) study urged researchers to move beyond the focus on just one type of beneficial behaviors in the online community, i.e., knowledge sharing or helping others. They suggested that identification with (i.e., attachment to) the groups in an online community leads to identification with the large online community as a whole, which in turn leads to participation and retention.…”
Section: Summary Of the Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Accordingly, a possible explanation for the difference is that some expectant mothers are more easily induced to feel happy and satisfied with online social life given the same level of self-esteem. Ren et al's (2012) study urged researchers to move beyond the focus on just one type of beneficial behaviors in the online community, i.e., knowledge sharing or helping others. They suggested that identification with (i.e., attachment to) the groups in an online community leads to identification with the large online community as a whole, which in turn leads to participation and retention.…”
Section: Summary Of the Resultsmentioning
confidence: 99%
“…The social support path links social support to coping resources, subjective well-being and OCCB, whereas the social identity path links characteristics of the online support community to community identification and OCCB. Although prior research has discussed the impact of various characteristics of online communities on identification (e.g., Ren et al, 2012), we are aware of no study which has tested the underlying causal mechanism or empirically confirmed the impact of online social support on subjective well-being. Our findings, based on survey data collected from 159 users of online support communities, support the assertion that social support and the characteristics of online support communities are crucial determinants of subjective well-being and community identification, respectively, both of which foster OCCB.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Given the importance of visual appeal in influencing thoughts and behaviors (Liu et al 2013), it may also motivate more social interactions among customers. These social interactions bring customers together and facilitate them to build stronger interpersonal bonds, that is, creating, enhancing, and sustaining ties among them (Kreijns et al 2007, Ren et al 2012). Hence, we hypothesize:…”
Section: Effects Of Ar Cuesmentioning
confidence: 98%
“…Therefore, visual appeal of a site fulfills customers' needs and acts as a significant switching cost for customers who become to depend on it (Schau et al 2009). This will instill and strengthen their feelings of belongingness and social identification with this site (Ren et al 2012). Given the importance of visual appeal in influencing thoughts and behaviors (Liu et al 2013), it may also motivate more social interactions among customers.…”
Section: Effects Of Ar Cuesmentioning
confidence: 98%